Mathematics for Ecology and Environmental Sciences - Takeuchi, Yasuhiro; Iwasa, Yoh.; Sato, Kazunori; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2007)
Dynamical systems theory in mathematical biology has attracted much attention from many scientific directions. The purpose of this volume is to discuss the many rich and interesting properties of dynamical systems that appear in ecology and environmental sciences. The main topics include population dynamics with dispersal, nonlinear discrete population dynamics, structured population models, mathematical models in evolutionary ecology, stochastic spatial models in ecology, game dynamics and the chemostat model. Each chapter will serve to introduce students and scholars to the state-of-the-art in an exciting area, to present important new results, and to inspire future contributions to mathematical modeling in ecology and environmental sciences.
Ecology as a Modern Science -- Physiologically Structured Population Models: Towards a General Mathematical Theory -- A Survey of Indirect Reciprocity -- The Effects of Migration on Persistence and Extinction -- Sexual Reproduction Process on One-Dimensional Stochastic Lattice Model -- A Mathematical Model of Gene Transfer in a Biofilm -- Nonlinearity and Stochasticity in Population Dynamics -- The Adaptive Dynamics of Community Structure.
Keywords: Mathematics; Ecology; Community ecology, Biotic; Applied mathematics; Engineering mathematics; Biomathematics; Statistical physics; Dynamical systems; Mathematics; Mathematical and Computational Biology; Applications of Mathematics; Ecology; Community & Population Ecology; Genetics and Population Dynamics; Statistical Physics, Dynamical Systems and Complexity; Electronic books